(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article analyzes the content, functions and characteristics of the balance sheet of budget organizations, accounting accounts, their structure and categories, documents used in accounting in accounting organizations, forms of accounting in budget organizations. Development and accounting of budget organizations. proposals for implementation using economic systems have been developed.